Fatal offences versus Przestępstwa przeciwko życiu: the degree of equivalence of the terms: murder, manslaughter, zabójstwo and nieumyślne spowodowanie śmierci - Matusiak, Rafał Krzysztof (Papers in Linguistics, 2025)
The article offers insight into the distinctions between various types of homicide made in the English and Polish legal systems. The general term homicide semantically encompasses all kinds of acts that result in the death of another person, regardless of whether they were committed intentionally or unintentionally, unlawfully or under the right of self-defence. The criminalised form of homicide is typically divided into two main crimes: murder and manslaughter. The English term murder has no statutory definition and is traditionally cited after Sir Edward Coke (1797). Initially, one can have an illusory impression that the Polish term zabójstwo fully corresponds to English murder. Nevertheless, as demonstrated in the article, even as regards the seemingly isosemantic terms of crimes, it is possible to discern differences between their features in both legal systems. Similarly, the term manslaughter does not have a statutory definition, and its scope of meaning can be reconstructed based on the boundaries of various mitigating circumstances (defences), which are to be found in numerous laws and court rulings. Hence, the term manslaughter covers six types of criminal acts. The juridical-semantic problem appears when it comes to finding functional equivalents for particular kinds of manslaughter in the Polish language and the Polish Penal Code. Thus, the article can be of interest to both legal discourse analysts and legal translators, and it may stimulate discussion on the (un)translatability of asymmetrical legal concepts.